Pyoderma Gangrenosum with Positive Antinuclear Antibody, in the Absence of Systemic Association - Shrestha, Smriti; Aryal, Alisha (Nepal Journal of Dermatology, Venereology & Leprology, 2018)
Pyoderma gangrenosum is an uncommon neutrophilic dermatosis, seen on legs, and infrequently on hands and other anatomical sites. It is associated with systemic diseases in 50-70% of the cases. Antinuclear antibody (ANA) seropositivity has been reported in pyoderma gangrenosum associated with connective tissue disorders. However, there are very few case reports of pyoderma gangrenosum in patients of systemic lupus erythematosus, while we did not find any reports of ANA seropositivity in isolated pyoderma gangrenosum. Hence, we report this unique case of pyoderma gangrenosum with classical clinicohistopathology, positive ANA but no systemic association. As anticipated, our patient responded promptly to steroids.